STUDI KASUS: TERAPI RENDAM AIR HANGAT UNTUK EDEMA TUNGKAI PADA IBU HAMIL TRIMESTER III - Kristiova Masnita Saragih; Ruth Sanaya Siagian (Jurnal Kebidanan, 2021)
About 80% of pregnant women experience leg edema in the third trimester of pregnancy. It is associated with a number of activity limitations. Immersion in warm water represents potential intervention to eliminate or minimize some of the functional limitations associated with leg edema during pregnancy. This case study describes leg edema in Mrs. M, 29 years old, a multigravida woman, 39-40 weeks gestation. Mrs. M was given counseling and warm water immersion on the legs to reduce edema that she experienced. Observations of leg edema were carried out through interview and physical examination. Warm water immersion was given routinely once a day for 10 minutes. After 5 consecutive days, Mrs. M said that her leg edema reduced day by day and she was happy with her condition. This study case showed that warm water immersion can reduce leg edema during pregnancy. The appropriate procedure of warm water immersion should be implemented to get the best result of intervention.